2016
DOI: 10.4081/jphia.2016.528
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and practice of self breast examination among female nurses at the Federal Teaching Hospital Ido-Ekiti, Nigeria

Abstract: Breast cancer is the most common female malignancy linked with high levels of morbidity and mortality in developing countries due to delayed diagnosis. This research assessed the knowledge of signs and risk factors of breast cancer and practice of self breast examination (SBE) among female nurses in a rural tertiary Hospital. Eighty-five nurses ages 20 to 60 years were sampled by simple randomization over a period of eight weeks through a self-administered semi-structured questionnaire. The analysis was done u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The term breast awareness is now used to describe a woman’s familiarity with her breasts and it has been suggested that periodic consistent self-breast examination (SBE) may facilitate this awareness (Allen, Tiffany, Groningen, & McCarthy, 2010). However, in Nigeria, SBE is still encouraged among women and adolescent girls for early detection of breast cancer (Gabriel et al, 2016). Self-breast examination is emphasized during reproductive education in Nigeria in contrast to CBE in developed nations where CBE and mammography are readily available, accessible, and affordable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term breast awareness is now used to describe a woman’s familiarity with her breasts and it has been suggested that periodic consistent self-breast examination (SBE) may facilitate this awareness (Allen, Tiffany, Groningen, & McCarthy, 2010). However, in Nigeria, SBE is still encouraged among women and adolescent girls for early detection of breast cancer (Gabriel et al, 2016). Self-breast examination is emphasized during reproductive education in Nigeria in contrast to CBE in developed nations where CBE and mammography are readily available, accessible, and affordable.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, tests for detecting breast cancer such as mammography and CBE are usually expensive and not readily available due to the low gross domestic product of the nation (National Bureau of Statistics, 2015). Studies in Nigeria have also shown that SBE is an effective practice that has led to the detection of breast cancer among large number of women (Gabriel et al, 2016; Oluwatosin, 2012). Hence, women and girls are therefore encouraged to regularly carry out SBE for early detection of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…English version of structured self-administered questionnaire was adopted from similar studies in developing countries Nigeria [17,18]; Sudan [19]; Morocco [20] and Wollega University of Ethiopia [21] used to collect information. Pre-testing was conducted on 5% of the sample size at Adare general hospital in Hawassa town and based on the result necessary amendments were made.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…16,17,18 One study found only 38.2% of doctors and 18.9% of nurses knew that increasing age was a risk factor for breast cancer. 16 Thus, Nigerian health workers may fail to offer mammography screening to women with negative age-related risk factors.…”
Section: Educational Challengesmentioning
confidence: 99%